"The Belt and Road" international migration of Asia research on multilateral population security - Mi, Hong 1962-; Li, Yuan 1972-; Ma, Qiyini 1993- (Routledge, 2022)
"The book studies multilateral population security issues and relevant governance strategies caused by international migration in the countries impacted by China's Belt and Road Initiative and their border areas. Buttressed by solid data mining and policy analysis, the title looks into the demographic trends of international migration in China and some Asian Belt and Road countries and stresses the urgency for more effective governance practices. Seeking to address the population security crisis triggered by the Initiative, the authors propose the idea of "multilateral population security governance", grounded in the real-world challenges facing Belt and Road countries while also drawing on experiences of migration governance in western countries. As a new governance model, it calls for cross-border joint action and takes into consideration pertinent factors including economy, politics, culture, religion and commerce. Several case studies and comparative studies are offered in the chapters to illuminate the significance and effect of this cooperative mechanism. The book will be of interest to researchers and government officials interested in non-traditional security, international migration and formal demography as well as topics on population, resources and environment"--
Keywords: One-Belt-One-Road-Initiative; Bevölkerungspolitik; Migration; Asien; China; China / Emigration and immigration / Government policy; Asia / Emigration and immigration / Government policy; Human security / China; Human security / Asia; Yi dai yi lu (Initiative : China); Emigration and immigration / Government policy; Human security; Asia